From ‘intercultural-washing’ to meaningful intercultural education: Revisiting higher education practice - Sommier, Mélodine; Lahti, Malgorzata; Roiha, Anssi (Journal of Praxis in Higher Education, 2021)
This is the first special issue that JPHE hosts—and could there be a more suitable forum for an issue dedicated to exploring and encouraging a critical dialogue around transformative intercultural communication teaching practices in higher education (HE)? What has led us to engage with the theme of making intercultural education meaningful is a shared observation that there seems to be an increasing disconnect between recent developments in intercultural communication theory and practice. With so much critique published over the years, we are perplexed as to why traditional notions of culture still prevail not only in mainstream intercultural communication research but also in institutional discourses in HE and in popular discourses as articulated by the people who sit—or have once sat—in our classrooms. In this editorial and Special Issue, we approach intercultural communication from a critical angle, akin to the theorization of interculturality as a discursive and contingent, unstable and contradictory, political and ideological construct. We are thrilled to see this approach gain ground in the field of intercultural communication. However, at the same time, we are worried that the terrain of intercultural communication teaching across HE settings has become quite unruly and is characterized by pedagogical solutions that do not have a stable connection to state-of-the-art theory, and that might lead to naive, simplistic, and essentialist understandings of ‘culture’ and ‘the other’.......